AN INVESTIGATION OF MALAYSIAN AIRLINE PASSENGERS TOWARDS THE WILLINGNESS TO PAY FOR AIRLINES CARBON OFFSET BASED ON FREQUENCY AND TRIP PURPOSES - Nur Fatihah Shaari; Muhammad Majid; Mohamad Faizal Ramli; Basri Badyalina; NurKhairany Amyra Mokhtar; Abdullah Mohamad (Journal of Islamic, Social, Economics and Development, 2022)
Greenhouse gas (GHG) emissions have quickly become a major concern in the automotive industry. About 2% of all man-made greenhouse gas emissions originate in the aviation industry. The transportation industry is concerned about several challenges, including reducing greenhouse gas emissions from air transportation. The aviation industry has launched several initiatives to cut carbon emissions, including a carbon offset scheme. However, the notion of carbon offset is a new method in Malaysia. Thus, the acceptance of carbon offset is still doubtful. The value of willingness to pay among Malaysian airline passengers is quantified by looking at the frequency and trip purposes. The mean willingness to pay is RM32.27 per trip, showing that Malaysian are willing to pay for this amount as an added value on top of their airfare. The result of this study can be insightful information and guideline for aviation industries and policymakers to develop and implement carbon offset in Malaysia.